TES HIV/AIDS TERHADAP CALON PENGANTIN DALAM PERSPEKTIF HUKUM ISLAM - Asep Saepullah; Mohammad Rana; Irfan Dzikri Abdillah, (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
Marriage is a sacred event in the course of one's life and the quality of a marriage is largely determined by the readiness and maturity of the two brides to prepare and manage household life towards the creation of a family that is sakinah, mawaddah and full of grace. For that it is necessary to first recognize the new life that will be experienced later to prospective husbands or wives, so that in time it can anticipate problems that arise later can be minimized, for that brides really need to take a brief debriefing about HIV/AIDS and carry out testing HIV/AID in the form of a bride and groom course which is one of the important and strategic efforts.This research aims to answer the questions that formulate the problem: How to examine HIV/AIDS tests on brides in KUA, Lemahwungkuk District, Cirebon City and How to Review Islamic Law on HIV/AIDS testing for brides conducted in KUA, Lemahwungkuk District, Cirebon City "This study uses qualitative research, data collected by means of interviews (interviews), documentation of observation then analyzed by descriptive analysis method.The results of this study: HIV/AIDS tests in the implementation of taking blood samples of bride and groom couples to get sex in the laboratory include blood tests, where the HV/AIDS test is one of the administrative requirements in marriage at the KUA office in Cirebon City of Lemahwungkuk. There are several benefits of doing HIV/AIDS tests on brides in the KUA of Lemahwungkuk District, Cirebon City, namely avoiding and preventing transmission of HIV/AIDS and IMS, maintaining and securing household peace, and fulfilling marital administration requirements at KUA, and as marriage administration requirements. HIV/AIDS testing is an application that is ijtihādiyyah, where its application is determined according to needs and benefits. This also gives space to the legal formation process which always changes depending on social dynamics and phenomena that occur. According to Islamic law the testing of HIV/AIDS against prospective brides in the KUA of Lemahwungkuk District in Cirebon City does not conflict with Islamic law. Because, it was done based on the principle of keep benefit.